Design an IoT Based Pratima Monitoring System - I Made Aris Aditya Nugraha; I Nyoman Piarsa; Kadek Suar Wibawa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2023)
Pratima is usually kept in temples or kept in sacred rooms. Lack of care and supervision causes easy cases of theft and damage due to fire. An Internet of Things-based pratima monitoring system is needed to avoid some of the threats that occur. Devices that are made connected to the internet for monitoring, and controlling monitoring devices so that Pratima remains safe. The Internet of Things-based pratima monitoring system is expected to be an early prevention system for acts of theft and damage due to fire. The results obtained are all the features successfully run. The measurement values of the ultrasonic sensor are 11CM and 16CM, while the ruler measurements are 10.5CM and 16CM. The temperature on the DHT22 is 70.50Â°C, and the flame sensor value is 123. The microwave sensor detects movement, and the image capture is stored on firebase and SD Card.